Prevalence and disparities in receiving medical advice to quit tobacco use in the US adult population - Chandra, Monalisa; Talluri, Rajesh; Fokom Domgue, Joel; Shete, Sanjay (Frontiers in Public Health, 2024)
Introduction Evidence suggests that advice from health care professionals (HCP) increases the likelihood of quit attempts and successful quitting of tobacco use. However, previous studies primarily focussed on cigarette smoking and did not include all forms of tobacco products. This study aimed to investigate the prevalence and disparities in receiving HCP’s advice to quit tobacco use (combustible or noncombustible) in the US adult population. Methods Using the 2022 National Health Information Survey (NHIS) data, we examined 4,424 adults who reported (i) any tobacco product use within the past 12 months and (ii) having seen an HCP within the past 12 months. The outcome variable included the receipt of advice to quit tobacco use from an HCP, and predictors included sociodemographic variables. Weighted prevalence estimates were calculated, and multivariable regression analyses were conducted. Results Over 38% of tobacco users who visited an HCP were advised to quit. The odds of receiving such advice were lower among Hispanics (AOR: 0.625; 95% confidence interval (CI) [0.464–0.843];p = 0.002), males (AOR: 0.767; 95% CI [0.659–0.893], p = 0.001), those above the poverty level (AOR: 0.795; 95% CI [0.641–0.987];p = 0.037), foreign-born (AOR: 0.664; 95% CI [0.496–0.888]; p = 0.006), those with a bachelor’s degree or higher educational level (AOR: 0.477; 95% CI [0.349–0.653]; p < 0.001) and those aged less than 45 years (AOR: 0.404; 95% CI: [0.344–0.473]; p < 0.001). Conclusion The prevalence of receiving HCP’s advice to quit tobacco use remains suboptimal and disparate among sociodemographic groups. Our findings call for strategic implementation of the USPHS’s recommendation on treating tobacco use and taking further actions to equip HCPs with the training and resources needed to provide appropriate advice to quit tobacco.